EffortsTo Improve Students' Learning Outcomes Through The Tgt (Teams Games Tournament) Type Cooperative Learning Model In Islamic Education Learning At Private Elementary School 101820 Bina Karya - Hamka; Sari, Siti Anna (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2025)
This study aims to analyze the effectiveness of the TGT (Teams Games Tournament) cooperative learning model in improving student learning outcomes on compulsory fasting material at SDS No.101820 Bina Karya. TGT is a learning model that will provide new experiences in learning so that they can understand the material more easily. In this study, the method used is Classroom Action Research (CAR) with a quantitative approach. Data were collected through observation, learning outcome tests and interviews to assess the development of students' understanding of compulsory fasting material before and after the implementation of TGT. The support provided by teachers in implementing TGT can also increase student activity in learning and understanding the material taught with methods that can attract students' interest in learning so that it can improve student learning outcomes on compulsory fasting material in class VI.